The Singing Class in times of crisis: Action guidelines for Singing Therapy and Counseling - Llanos López de Castilla, Jimena (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The goal is the creation of a methodology to approach voice students by facilitating the learning of vocal didactics from the prospective of Singing Therapy and Counseling, which would help voice teachers when working with their students in times of personal or collective crisis. This study will analyse the results of a questionnaire involving ten students who followed the course from 2020 to 2022. The Seven Basic Moments of the Singing Class have been linked to Hobfoll’s Five Essential Elements of Immediate and Mid-Term Mass Trauma Intervention.